Current Approaches and Molecular Mechanisms for Directly Reprogramming Fibroblasts Into Neurons and Dopamine Neurons - Han, Fabin; Liu, Yanming; Huang, Jin; Zhang, Xiaoping; Wei, Chuanfei (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease is mainly caused by specific degeneration of dopaminergic neurons (DA neurons) in the substantia nigra of the middle brain. Over the past two decades, transplantation of neural stem cells (NSCs) from fetal brain-derived neural stem cells (fNSCs), human embryonic stem cells (hESCs), and induced pluripotent stem cells (iPSCs) has been shown to improve the symptoms of motor dysfunction in Parkinson’s disease (PD) animal models and PD patients significantly. However, there are ethical concerns with fNSCs and hESCs and there is an issue of rejection by the immune system, and the iPSCs may involve tumorigenicity caused by the integration of the transgenes. Recent studies have shown that somatic fibroblasts can be directly reprogrammed to NSCs, neurons, and specific dopamine neurons. Directly induced neurons (iN) or induced DA neurons (iDANs) from somatic fibroblasts have several advantages over iPSC cells. The neurons produced by direct transdifferentiation do not pass through a pluripotent state. Therefore, direct reprogramming can generate patient-specific cells, and it can overcome the safety problems of rejection by the immune system and teratoma formation related to hESCs and iPSCs. However, there are some critical issues such as the low efficiency of direct reprogramming, biological functions, and risks from the directly converted neurons, which hinder their clinical applications. Here, the recent progress in methods, mechanisms, and future challenges of directly reprogramming somatic fibroblasts into neurons or dopamine neurons were summarized to speed up the clinical translation of these directly converted neural cells to treat PD and other neurodegenerative diseases.